PERANCANGAN SISTEM ANTRIAN DENGAN SPEECH RECOGNITION BERBASIS WEB PADA PUSKESMAS GASAN GADANG KAB. PADANG PARIAMAN - Mutia Azizah; Harry Setya Hadi (Jurnal Manajemen Teknologi Informatika, 2024)
The research is aimed at designing and implementing a web-based antenna System with voice features in Puskesmas Gasan Gadang, Padang Pariaman district. The System is expected to improve the efficiency and convenience of the enclosure process, as well as provide ease of access for the public. The method used in the design of this System is the Waterfall method, which covers the stages of needs analysis, System design, Implementation, testing, and Maintenance. System design is done using the Unified Modeling Language (UML) to model various aspects of the System, including Use Case diagrams, Activity diagram, class diagram and Sequence diagram. The System Implementation utilizes text-to-speech (TTS) and speech recognition technologies to provide user-friendly notifications and voice interactions. Implementation results show that the System can improve the efficiency of the pending process by reducing waiting times and providing real-time notifications to users. System testing also showed that the voice feature is running well and provides additional accessibility for users. Based on the results, the System is expected to be widely adopted in a variety of other health services to improve the quality of attendance services.